THE IDENTITY OF THE HYBRIDITY OF THE CHINESE MUSLIM MOSQUE IN SEMPUSARI, JEMBER (CHARLES SANDERS PIERCE SEMIOTIC ANALYSIS) - Fauziyanti, Eva (QAULAN: Journal of Islamic Communication, 2022)
Abstract: Religion and culture are two things that are always interesting to observe. It is difficult to imagine religion without culture or vice versa, culture without religion. In human history, religion and culture work hand in hand to preserve society with various legal arrangements. In Islam contains a number of teachings that are not limited to aspects of civilization. One example is the Muhammad Cheng Hoo mosque in Sempusari Jember, whose architecture is combined with Chinese, Javanese and Arabic culture. The Chinese identity was reborn after a post-reformation that was lost for decades. This study aims to describe the architectural meaning in the Cheng Hoo mosque in Sempusari Jember. To get the desired results, this research uses qualitative research with a descriptive approach, based on observation, interview, and documentation techniques. Meanwhile, to find out the existing cultural values, the writer uses the theory of cultural semiotics by Sander Pierce. The findings obtained from this study are a study of the meaning of cultural semiotics in the Cheng Hoo mosque architecture in Sempusari Jember including (a) the colors used. (b) An octagonal shape located in the middle of the Cheng Hoo Mosque. (c) Tower consisting of 5 flats. (d) the meaning of the lantern. (e) The shape on the walls of the mosque on the part of the imam and pulpit. (f) Flower motif. (g) the writing on the door of the mosque in Roman kanji style.